La comunicación de las ideas después del 11-S: el clamor de todas las preguntas - Casals Carro, María Jesús (Estudios sobre el Mensaje Periodístico, 2002)
Ever since the ancient Greeks it is known that the persuasion is obtained by the implicit meaning of the dominant speech. But that persuasion becomes manipulation when deceptive expressions are used in order to hide those realities that are not convenient to explain in all their reach. This article intend to study this phenomenon, highly present in the political speeches after the attack of September 11th, and its negative consequences for the exercise of the freedom of thought and the freedom of expression, paradigms both of the democratic societies where they were born like concept of the most elementary human dignity.